Amphoteric Indium Enables Carrier Engineering to Enhance the Power Factor and Thermoelectric Performance in n‐Type AgnPb100InnTe100+2n (LIST). Issue 17 (7th March 2019) - Xiao, Yu; Wu, Haijun; Wang, Dongyang; Niu, Changlei; Pei, Yanling; Zhang, Yang; Spanopoulos, Ioannis; Witting, Ian Thomas; Li, Xin; Pennycook, Stephen J.; Snyder, Gerald Jeffrey; Kanatzidis, Mercouri G.; et al.
Abstract: The Ag and In co‐doped PbTe, Ag n Pb100 In n Te100+2 n (LIST), exhibits n ‐type behavior and features unique inherent electronic levels that induce self‐tuning carrier density. Results show that In is amphoteric in the LIST, forming both In 3+ and In 1+ centers. Through unique interplay of valence fluctuations in the In centers and conduction band filling, the electron carrier density can be increased from ≈3.1 × 10 18 cm −3 at 323 K to ≈2.4 × 10 19 cm −3 at 820 K, leading to large power factors peaking at ≈16.0 µWcm −1 K −2 at 873 K. The lone pair of electrons from In + can be thermally continuously promoted into the conduction band forming In 3+, consistent with the amphoteric character of In. Moreover, with rising temperature, the Fermi level shifts into the conduction band, which enlarges the optical band gap based on the Moss–Burstein effect, and reduces bipolar diffusion and thermal conductivity. Adding extra Ag in LIST improves the electrical transport properties and meanwhile lowers the lattice thermal conductivity to ≈0.40 Wm −1 K −1 . The addition of Ag creates spindle‐shaped Ag2 Te nanoprecipitates and atomic‐scale interstitials that scatter a broader set of phonons. As a result, a maximum ZT value ≈1.5 at 873 K is achieved in Ag6 Pb100 InTe102 (LIST). Abstract : Ag and In co‐doped PbTe, Ag n Pb100 In n Te100+2 n (LIST), exhibits a promising thermoelectric performance. Both a high power factor and low thermal conductivity are achieved in LIST enabled by the amphoteric In, and the In impurity level induces self‐tuning carrier density to suppress bipolar diffusion based on the Moss–Burstein effect. As a result, a maximum ZT value of ≈1.5 is achieved in LIST.